PEMBELAJARAN JARAK JAUH DENGAN METODE KIP (KREATIF, INOVATIF, DAN PRODUKTIF) PADA MASA PANDEMI UNTUK SISWA SEKOLAH DASAR - Ayu Fahmi Rosydianah; Achmad Room Fitrianto; Abdul Karim Hasibuan; M Fathullah (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Education is the backbone of the nation's progress. Because a good education can create quality human resources (HR). The distance learning process carried out during a pandemic can trigger a decrease in participation and active interest in learning. Therefore, optimal encouragement and support are needed to restore the active learning of students. Creative, innovative and productive learning methods are designed to deal with the process of changing the way learning is carried out remotely. KIP method (creative, innovative and productive) method is based on constructivism theory. This method only facilitates students to build new concepts based on the old concepts they already have. there we conduct tutoring activities which are held for 2 weeks, the management strategy approach is in the form of tutoring. The difference that we make is with the existence of the smart game. The Creative, Innovative, and Productive methods applied to elementary school students in Bringinbendo Village, turned out to have brought changes in learning patterns. Students look more active in learning and more easily understand the material they have learned.